2021
DOI: 10.1002/hed.26660
|View full text |Cite
|
Sign up to set email alerts
|

Identification of risk factors for mortality and delayed oral dietary intake in patients with open drainage due to deep neck infections: Nationwide study using a Japanese inpatient database

Abstract: Backgrounds: Data on risk factors for deep neck infection (DNI) including descending necrotizing mediastinitis (DNM) have been limited. Using a nationwide database, the aim was to identify the factors related to patient death and delay in recovering oral intake. Methods: We retrospective reviewed a Japanese inpatient database between 2012 and 2017, and data of 4,949 patients with DNM and DNI were extracted. The main outcome was survival at discharge. In a subgroup analysis of the 4,791 patients with survival a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 40 publications
2
10
1
Order By: Relevance
“…Although it has been reported that resumption of oral intake is delayed in patients with descending necrotizing mediastinitis, there was no significant difference in FOIS for each period between patients with and those without mediastinal abscess in this study [13]. Thoracoscopic or thoracotomy drainage also did not affect FOIS in our study.…”
Section: Discussioncontrasting
confidence: 79%
“…Although it has been reported that resumption of oral intake is delayed in patients with descending necrotizing mediastinitis, there was no significant difference in FOIS for each period between patients with and those without mediastinal abscess in this study [13]. Thoracoscopic or thoracotomy drainage also did not affect FOIS in our study.…”
Section: Discussioncontrasting
confidence: 79%
“…Multiple logistic regression analysis was performed to compare multiple outcome categories, assessing the independent effect on the severity of intracranial complications. Inclusion of independent variables in the model was based on earlier research and existing knowledge in terms of the following risk factors for aggravation of intracranial complication and abscesses in the head and neck region (2)(3)(4)(5)11,14,21): age, sex, pathogenesis (cholesteatoma or other otitis media), type of complication (subdural abscess including cerebral abscess or other intracranial complications such as epidural abscess or meningitis), level of consciousness evaluated by the JCS, comorbid DM and sepsis, and repeated surgical interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Data were extracted from the Diagnostic Procedure Combination (DPC) database, a national inpatient database in Japan. The details of the DPC database have been described previously (12)(13)(14). Briefly, the DPC database includes administrative claims data and detailed medical data collected for all inpatients discharged from participating hospitals.…”
Section: Data Sourcementioning
confidence: 99%
See 1 more Smart Citation
“…BI at discharge was classified as under 59 and over 60. Age, smoking status, and BI were classified according to previous studies 16–19 . As for LOS, we used it as a continuous variable because there is no standard grouping method for LOS like BI and BMI.…”
Section: Methodsmentioning
confidence: 99%